1970
DOI: 10.1136/bmj.4.5737.724
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic secretion of parathyroid hormone by a renal adenocarcinoma in a patient with hypercalcaemia.

Abstract: Medical MemorandaMIDALeJOUWNL keratodermia spread to involve all four limbs, the back, the face, and the scalp. The lesions progressed from a macular eruption to vesicular and pustular stages, finally becoming hard scaling keratotic plaques, which on the feet were painful and irritating. Fresh lesions appeared adjacent to areas of healing ( Fig. 1), and in view of their severity oral prednisone 40 mg. daily and topical hydrocortisone were prescribed. The arthritis was also treated with indomethacin with partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(15 citation statements)
references
References 7 publications
(8 reference statements)
0
14
0
1
Order By: Relevance
“…Secondly, the level of hormone secreted may be low enough that a large mass of neoplastic tissue is necessary for detection of biologic activity. In support of the latter explanation is the observation that the parathyroid hormone content of malignant neoplasms in people with pseudohyperparathyroidism has ranged from only 0.75 to 8.9 pg per gram dry weight [5,16,23,44] as compared to 200 to 600 pg per gram dry weight in normal and adenomatous parathyroid tissue [20,44].…”
Section: Discussionmentioning
confidence: 48%
“…Secondly, the level of hormone secreted may be low enough that a large mass of neoplastic tissue is necessary for detection of biologic activity. In support of the latter explanation is the observation that the parathyroid hormone content of malignant neoplasms in people with pseudohyperparathyroidism has ranged from only 0.75 to 8.9 pg per gram dry weight [5,16,23,44] as compared to 200 to 600 pg per gram dry weight in normal and adenomatous parathyroid tissue [20,44].…”
Section: Discussionmentioning
confidence: 48%
“…However, nonparaneoplastic, bone metastasis-related hypercalcemia is also highly prevalent among RCC patients. Of those with hypercalcemia and RCC, approximately 75% have high-stage lesions and 50% bone metastasis [4,5] , although neither the presence nor degree of hypercalcemia has been shown to have a significant correlation with tumor grade or survival [6] .…”
Section: Paraneoplastic Hypercalcemiamentioning
confidence: 99%
“…Occasionally reported in association with bladder urothelial carcinoma (BCa) [3] , HHM is the most common PNS among patients with RCC, affecting between 13 and 20% of patients [4] . However, nonparaneoplastic, bone metastasis-related hypercalcemia is also highly prevalent among RCC patients.…”
Section: Paraneoplastic Hypercalcemiamentioning
confidence: 99%
“…The first direct support for this came from the first PTH radioimmunoassay, when Berson and Yalow (1966) found significantly elevated PTH levels in an unselected group of patients with bronchogenic carcinoma. There were subsequently several reports of measurement of PTH by radioimmunoassay in plasma or extracts of cancers from patients with this syndrome (Sherwood et al, 1967;Melick et al, 1972;Buckle et al, 1970), of an arteriovenous gradient of PTH across a tumour bed (Knill-Jones et al, 1970), and we showed that a cell culture established from a renal cortical carcinoma of a hypercalcaemia patient produced immunoreactive PTH (Greenberg et al, 1973). In none of these instances, however, was the circulating level of PTH as high as frequently found in patients with primary hyperparathyroidism and comparable degrees of elevated plasma calcium.…”
Section: Hypercalcaemia I N Cancermentioning
confidence: 99%